A virtual reality environment to support chat rooms for hearing impaired and to teach Brazilian Sign Language (LIBRAS) - Brega, José Remo Ferreira [UNESP]; Rodello, Ildeberto Aparecido; Dias, Diego Roberto Colombo; Martins, Valéria Farinazzo; De Paiva Guimarães, Marcelo (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Improving the way that totally or partially deaf people communicate with the world is a challenging task for our society. One way to improve their communication is to learn sign language, which is a visual language based on hand shapes, orientations, and movements of the hands, arms, or body, and facial expressions. This paper aims to present a 3D virtual reality environment to allow deaf users to communicate with each other in a real-time, synchronous, instantaneous fashion via an online chat room and to assist the teaching-learning process of Brazilian Sign Language (LIBRAS). A three-dimensional avatar was developed which can translate words or sentences from Portuguese to LIBRAS. It was performed two experiments to evaluate the communication via the chat room: (1) with chat history enabled (visible) and (2) with chat history disabled (invisible). These evaluations involved 30 end-users, which confirmed that the virtual environment as developed here is effective to distance classes.
Keywords: deaf people; hearing-impaired; LIBRAS; online chat; sign language